The unbeatable Squirrel Girl. Powers of a squirrel - North, Ryan, 1980- (Marvel Worldwide, 2019)
Doreen Green, aka Squirrel Girl, faces her biggest challenge yet when she majors in computer science at Empire State University. But with her pal Tippy-Toe by her side, she balances homework with fighting bad guys like Galactus, Kraven the Hunter, and Whiplash.